Relationship between Altered Platelet Morphological Parameters and Retinopathy in Patients with Type 2 Diabetes Mellitus - Tolga Yilmaz; Ahu Yilmaz (Journal of Ophthalmology)
Purpose. To investigate whether platelet morphology or function is altered in patients with diabetic retinopathy (DR). Methods. This prospective study enrolled 85 healthy controls (HCs) (group 1) and 262 patients with Type 2 diabetes mellitus (T2DM). Patients were subclassified into three groups according to ocular findings: no DR (group 2; n=88); nonproliferative DR (group 3; n=88), and proliferative DR (group 4; n=86). Mean platelet volume (MPV), platelet distribution width (PDW), platelet large cell ratio (PLCR), plateletcrit (PCT) values, and platelet count were measured in the studied groups. Results. MPV, PDW, and PLCR levels were significantly altered in groups 2–4 compared with HCs (p<0.05, p<0.05, p<0.05). Compared with group 2, both DR groups had higher MPV and PDW levels, with a significant difference between groups 2 and 4 for both MPV (p=0.036) and PDW (p=0.006). PLCR correlated with retinopathy stage, but no significant difference was found between the DR groups. Platelet count and PCT values were not significantly different between the groups (p>0.05). Conclusion. Our findings suggest an association between mean platelet indices (MPI) (i.e., MPV, PDW, and PLCR) and DR stage. Therefore, MPI could be a beneficial prognostic marker of DR in patients with T2DM.